Answer

Verified

456.3k+ views

Hint: Assume the cost of one pen and one pencil as some variable. Form simultaneous equations based on the data given and solve them.

Let the cost of one pen and one pencil is $Rs.x$ and $Rs.y$ respectively.

Then, according to the question, the cost of one pen and one pencil is Rs. 12. So, we have:

$

\Rightarrow x + y = 12, \\

\Rightarrow x = 12 - y .....(i) \\

$

Next, it is given that three pencils and five pens cost Rs.56. So, we have:

$ \Rightarrow 5x + 3y = 56 .....(ii)$

Putting the value of $x$ from equation $(i)$ into equation $(ii)$. We’ll get:

$

\Rightarrow 5\left( {12 - y} \right) + 3y = 56, \\

\Rightarrow 60 - 5y + 3y = 56, \\

\Rightarrow 2y = 4, \\

\Rightarrow y = 2 \\

$

Putting the value of $y$ in equation $(i)$ we’ll get:

$

\Rightarrow x = 12 - 2, \\

\Rightarrow x = 10 \\

$

Thus, the cost of one pen is Rs. 10 and that of one pencil is Rs. 2.

Note: We can solve simultaneous equations using the addition method also. In this, we try to make the coefficient of one of the variables same in both the equations by multiplying them with suitable constants. And then simply subtract any one equation from another to get a linear equation in one variable.

Let the cost of one pen and one pencil is $Rs.x$ and $Rs.y$ respectively.

Then, according to the question, the cost of one pen and one pencil is Rs. 12. So, we have:

$

\Rightarrow x + y = 12, \\

\Rightarrow x = 12 - y .....(i) \\

$

Next, it is given that three pencils and five pens cost Rs.56. So, we have:

$ \Rightarrow 5x + 3y = 56 .....(ii)$

Putting the value of $x$ from equation $(i)$ into equation $(ii)$. We’ll get:

$

\Rightarrow 5\left( {12 - y} \right) + 3y = 56, \\

\Rightarrow 60 - 5y + 3y = 56, \\

\Rightarrow 2y = 4, \\

\Rightarrow y = 2 \\

$

Putting the value of $y$ in equation $(i)$ we’ll get:

$

\Rightarrow x = 12 - 2, \\

\Rightarrow x = 10 \\

$

Thus, the cost of one pen is Rs. 10 and that of one pencil is Rs. 2.

Note: We can solve simultaneous equations using the addition method also. In this, we try to make the coefficient of one of the variables same in both the equations by multiplying them with suitable constants. And then simply subtract any one equation from another to get a linear equation in one variable.

Recently Updated Pages

She leaned back feeling enervated Choose the word which class 8 english CBSE

Fill the blank with an appropriate modal What cannot class 8 english CBSE

The English Education Act was introduced in the year class 8 social science CBSE

What is Kayal in Geography class 8 social science CBSE

Are book titles proper nouns class 8 english CBSE

Are numbers adjectives Is two or three an adjective class 8 english CBSE

Trending doubts

Fill the blanks with the suitable prepositions 1 The class 9 english CBSE

Which are the Top 10 Largest Countries of the World?

Give 10 examples for herbs , shrubs , climbers , creepers

Differentiate between homogeneous and heterogeneous class 12 chemistry CBSE

Difference between Prokaryotic cell and Eukaryotic class 11 biology CBSE

Write a letter to the principal requesting him to grant class 10 english CBSE

Difference Between Plant Cell and Animal Cell

The Equation xxx + 2 is Satisfied when x is Equal to Class 10 Maths

One cusec is equal to how many liters class 8 maths CBSE